Understanding and Negotiating Vocal and Communicative Congruence: A Mixed-Methods Study with Transgender and Gender Diverse People and Speech-Language Therapists - Lu, Chang-Jung (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2026)
This thesis examines how trans and gender diverse (TGD) people and speech- language therapists (SLTs) conceptualise and engage with vocal and communicative congruence in the context of voice and communication therapy. Study 1 employed a survey to investigate understandings of congruence and factors contributing to a sense of vocal alignment among TGD participants. The findings demonstrated that vocal and communicative congruence is deeply personal and extends beyond acoustic or technical parameters, encompassing identity, authenticity, safety, and the experience of being recognised and understood. Study 2 employed focus groups to discuss the perspectives of TGD people and SLTs. This provided insight into similarities and differences in the issues each group prioritised, offering a basis to interpret and work with these perspectives. The study indicated that more open and reflective communication is necessary in therapy, particularly at the early stages. Study 3 adopted an e-Delphi methodology to co-develop a clinical conversation toolkit aimed at supporting collaborative practices. Through iterative consultation with both TGD people and SLTs, the toolkit was refined to ensure clarity, respectfulness, and flexibility in clinical application. Collectively, the thesis advances understanding of vocal and communicative congruence as a multidimensional construct and provides an evidence-based resource to facilitate more collaborative, person-centred, and affirming therapeutic practice.
APPROVED
Keywords: Vocal identity; Voice therapy; Communication; Congruence; Transgender; Gender diversity